Deformation, dislocation evolution and the non-Schmid effect in body-centered-cubic single- and polycrystal tantalum. (April 2023) - Lee, Seunghyeon; Cho, Hansohl; Bronkhorst, Curt A.; Pokharel, Reeju; Brown, Donald W.; Clausen, Bjørn; Vogel, Sven C.; Anghel, Veronica; Gray, George T.; Mayeur, Jason R.
Abstract: A physically-informed continuum crystal plasticity model is presented to elucidate deformation mechanisms, dislocation evolution and the non-Schmid effect in body-centered-cubic (bcc) tantalum widely used as a key structural material for mechanical and thermal extremes. We show the unified structural modeling framework informed by mesoscopic dislocation dynamics simulations is capable of capturing salient features of the large inelastic behavior of tantalum at quasi-static (10 −3 s −1 ) to extreme strain rates (5000 s −1 ) and at low (77 K) to high temperatures (873 K) at both single- and polycrystal levels. We also present predictive capabilities of the model for microstructural evolution in the material. To this end, we investigate the effects of dislocation interactions on slip activities, instability and the non-Schmid behavior at the single crystal level. Furthermore, ex situ measurements on crystallographic texture evolution and dislocation density growth are carried out for polycrystal tantalum specimens at increasing strains. Numerical simulation results also support that the modeling framework is capable of capturing the main features of the polycrystal behavior over a wide range of strains, strain rates and temperatures. The theoretical, experimental and numerical results at both single- and polycrystal levels provide critical insight into the underlying physical pictures for micro- and macroscopic responses and their relations in this important class of refractory bcc materials undergoing large inelastic deformations. Highlights: A continuum crystal plasticity model is presented to elucidate deformation mechanisms in bcc tantalum. The unified model captures salient features at quasi-static ( 1 0 − 3 s − 1 ) to extreme strain rates (5000 s − 1 ) and at low (77 K) to high temperature (873 K) at both single- and polycrystal levels. We address slip instability mechanisms due to strong dislocation interactions in bcc single crystals. We further extend the single crystal model to account for the non-Schmid behavior strongly associated with slip instability. We report on evolutions of crystallographic texture and dislocation density measured via neutron diffraction and compare the experimental results against numerical simulations for bcc polycrystals.